Parent involvement and receptive language skills of children with visual impairment - Tanedo, Andrea P. (College of Education, University of the Philippines Diliman, 2014)
"This is a descriptive study on aspects of parental involvement, namely parents’ role construction, parents’ self-efficacy, parents’ perception of involvement, and their relationship to the receptive language skills of children with visual impairment (CVI). Parents’ activities done at home and in school were also examined in relation to the receptive language skills of their children with visual impairment. Thirty-three parents and their pre-school level children were included in the sample. Using the Spearman Rho test, it was found that there was a strong significant positive relationship between parental involvement and receptive language skills among three and eight-year old children with visual impairment. Three and eight-year old children’s receptive language skills were positively correlated with their parents’ role construction, self-efficacy, and perception on involvement. In contrast, the five-year old children’s receptive language skills were negatively correlated with parents’ role construction and parents’ self-efficacy. Six-year old children’s receptive language skills were likewise negatively correlated with parents’ perception of involvement. In the focus group discussion, results showed that the most common activity done by parents at home was assisting their children’s learning. Parents reviewed lessons and helped their children in doing assignments. In school activities, the parents were most frequently involved in assisting children’s academics, such as guiding and prompting during table-top activities." --